RESEARCH ON PHOTOVOLTAICS: REVIEW, TRENDS AND PERSPECTIVES - Brito, Moacyr A. G. de [UNESP]; Sampaio, Leonardo P. [UNESP]; Junior, Luigi G. [UNESP]; Canesin, Carlos A. [UNESP]; IEEE (Ieee, 2011)
This paper presents a briefly review, some trends and perspectives in the field of Photovoltaic energy conversion, which is considered to be the most important renewable energy source in few years, in the coming decades. The power electronics plays a fundamental role in this process, developing systems each times more competitive, efficient, reliable, and also reducing costs and reducing the payback time. Some trends are visible, which are the use of Silicon Carbide devices in PV inverters, the use of integrated inverter structures, the integration of power converters into the PV module or the use of few PV series connection, the development of thinner and more efficient solar cells. Moreover, the discussion about the necessity of MPPT and anti-island schemes are presented, mainly considering the expected growth of grid-tied applications.
Keywords: Photovoltaic Energy; Renewable Energy; Integrated Converters; Solar Inverters; Trends and Concepts on PV; Power Electronics